Tinjauan Yuridis terhadap Tindak Pidana Kekerasan dalam Rumah Tangga: Studi Kasus Putusan No. 666 K/Pid.Sus/2018 - Apriliani Dewi Susana; Idris Rifandi (El-Mujtama: Jurnal Pengabdian Masyarakat, 2021)
These various forms of violence emerge in patterns of power relations within the household, between members of the household which are unequal (asymmetrical). Because the relationship pattern in the household is built on trust, when violence occurs in the household, two consequences actually occur at once, namely abuse of power and abuse of trust. Concretely, domestic violence refers to forms of violence such as rape or other sexual violence against wives (material rape) or children and even household servants carried out by employers. Other forms of violence, such as beatings or torture (both physical and psychological/verbal), and in various forms carried out by someone against a child or wife/husband or partner of a domestic helper. In this research, the author uses a normative research method, namely research by analyzing applicable legal norms, both in the form of laws and court decisions. Research data was obtained from library materials and legal documentation in the form of primary law, namely: the 1945 Constitution of the Republic of Indonesia, the Criminal Code (KUHP), the Criminal Procedure Code (KUHAP), Laws No. 23 of 2004 concerning the Elimination of Domestic Violence, as well as Decision no. 666 K/Pid. Sus/2018, Secondary Law, namely books about the Constitution, opinions that are relevant to the problems studied, as well as tertiary law, namely the Big Indonesian Dictionary, Law Dictionary and various other relevant dictionaries. The results of this research show that incidents of domestic violence (KDRT) are dominated by the wife as the victim. Domestic violence is closely related to gender issues, discrimination against women, and is identified with personal problems within a family. Violence committed by husbands against wives is not only physical violence, but also psychological, economic and sexual violence. Law enforcement can do its best to deal with violence committed by husbands against wives. Both by carrying out penal and non-penal countermeasures. So that obstacles in resolving violence committed by husbands against wives can be overcome. Therefore, the panel of judges decided that the defendant must be declared to have been legally and convincingly proven to have committed the crime of committing an act of physical violence in the domestic sphere which resulted in the victim becoming ill or seriously injured as charged in the first alternative indictment, based on the facts described in the trial, thus this element has been fulfilled according to the law. Because all the elements of Article 44 paragraph (2) of Law Number 23 of 2004 have been fulfilled. And during the trial, the Panel of Judges did not find anything that could eliminate criminal responsibility, either as a justification or excuse, so the Defendant must be held accountable for his actions.